2012
DOI: 10.1038/cdd.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Two-step activation of FOXO3 by AMPK generates a coherent feed-forward loop determining excitotoxic cell fate

Abstract: Cerebral ischemia and excitotoxic injury induce transient or permanent bioenergetic failure, and may result in neuronal apoptosis or necrosis. We have previously shown that ATP depletion and activation of AMP-activated protein kinase (AMPK) during excitotoxic injury induces neuronal apoptosis by transcription of the pro-apoptotic BH3-only protein, Bim. AMPK, however, also exerts pro-survival functions in neurons. The molecular switches that determine these differential outcomes are not well understood. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 41 publications
2
44
0
2
Order By: Relevance
“…Numerous studies have also suggested that metformin inhibits cardiac and renal fibrosis by regulating the TGFβ signaling pathway, which is important in fibrosis [12,42]. FOXO3, which is regulated by the AMPK signaling pathway [43,44], has been found to be an important mediator of TGFβ gene expression [45]. Moreover, the PI3K-AKT signaling pathway negatively regulates the pro-apoptotic forkhead transcription factors (FOXO) [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also suggested that metformin inhibits cardiac and renal fibrosis by regulating the TGFβ signaling pathway, which is important in fibrosis [12,42]. FOXO3, which is regulated by the AMPK signaling pathway [43,44], has been found to be an important mediator of TGFβ gene expression [45]. Moreover, the PI3K-AKT signaling pathway negatively regulates the pro-apoptotic forkhead transcription factors (FOXO) [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Specific PTMs regulate the partitioning of FOXO3 between the cytosol and the nucleus [8][9][10][11][12][13][14][15] and its stability and degradation, 16 but the links between specific PTMs and FOXO3 transcriptional specificity are less well understood.…”
mentioning
confidence: 99%
“…Several upstream kinases have been implicated in the phosphorylation and activation of AMPK, including LKB1 and Ca 2+ /calmodulin-dependent kinase kinase β (CaMKKβ) [14]. The phosphorylation of AMPK by LKB1 is enhanced by AMP [15], and this may be an important pathway by which AMPK can be activated to maintain metabolic homeostasis. In particular, LKB1 appears to predominantly target the a2 isoform [13].…”
Section: Discussionmentioning
confidence: 99%
“…All motor function and reflexes as typical neurological manifestations of brain injury were evaluated using the neurological severity score (NSS). Neurological function was graded on a scale of 0-18 (normal score, 0; mild injury score, 1-6; moderate injury score, 7-12; severe injury score, [13][14][15][16][17][18]. The NSS consists of motor, sensory, reflex and balance tests.…”
Section: Neurological Scoringmentioning
confidence: 99%